Concrete Compressive Strength Study with Anadara granosa Shell Waste as a Replacement for Part of Cement - Safarizki, Hendramawat Aski (Science and Technology Research Centre, Universitas PGRI Semarang, 2020)
Concrete is the main component of construction materials in Indonesia. Concrete composition materials consist of cement, sand, gravel, and water. Cement production in Indonesia in fact often causes polemic in the community. The community often complains of environmental pollution resulting in the cement production process. Shellfish from various mollusks like that are available abundantly along the coastal areas in Indonesia. Blood clam (Anadara granosa) is one of the many shells found in Indonesian waters and is consumed by many people because of its high protein content. Shells are part of the clam that cannot be consumed so they only accumulate into household waste. Seashell waste can be an environmental problem if not handled properly. The conch shell contains lime, silicate and alumina. The aim of this study was to determine the effect of the Anadara granosa shell as a substitute for a portion of cement in the manufacture of normal concrete. Stages of research conducted in the form of making normal concrete without any added material, making concrete with Anadara granosa shell as a partial replacement for cement, and testing the compressive strength of normal concrete samples. The optimum level of Anadara granosa shell waste as a substitute material for a portion of normal mixed concrete cement is 3% of the weight of cement used. The optimum compressive strength of concrete with Blood Shells waste as a substitute for some cement is at 30.62 MPa. The effect of Anadara granosa shell as a partial cement substitute in making normal concrete can reduce the compressive strength along with the addition of Anadara granosa shell as a partial cement substitute. Keywords: blood shells, cement, compressive strength, concrete